2011
DOI: 10.4317/medoral.17093
|View full text |Cite
|
Sign up to set email alerts
|

Tooth size changes with age in a Spanish population: Percentile tables

Abstract: Objectives: The aims of this work were: firstly, to draw up tables of percentile tooth sizes similar to those of Sanin and Savara for three age groups of a Spanish population; secondly, to describe changes in tooth size between those groups over time, as well as observing any sexual dimorphism and, finally, to compare both the Spanish and Sanin and Savara's American population samples. Material and methods: The sample included 359 patients and was divided into three age groups: adolescents, young adults and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
(8 reference statements)
0
13
0
Order By: Relevance
“…A significant reduction in the mesiodistal tooth size was observed over the 47year follow-up (Table IV), corroborating previous studies that reported an interproximal wear and reduction in the tooth size. 15,16,34 However, no study followed untreated individuals with a normal occlusion. A mean reduction of 0.35 mm in the mesiodistal tooth size was found in the present study from 13 to 60 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant reduction in the mesiodistal tooth size was observed over the 47year follow-up (Table IV), corroborating previous studies that reported an interproximal wear and reduction in the tooth size. 15,16,34 However, no study followed untreated individuals with a normal occlusion. A mean reduction of 0.35 mm in the mesiodistal tooth size was found in the present study from 13 to 60 years.…”
Section: Discussionmentioning
confidence: 99%
“…14 Decrease in the mesiodistal tooth size as a result of interproximal attrition with age was previously described. [14][15][16] Begg reported a 10.5 mm mesiodistal tooth wear in the lower arch in primitive Australian aborigines. 15,17 A mean reduction of 0.15 and 0.32 mm per tooth was described from adolescence to 50 years of age in modern civilization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Some authors have reported that sexual dimorphism is significant in adults but not in adolescents, and age would therefore appear to be a relevant factor for establishing the sex discrimination potential of teeth. 40 The delay in tooth maturation and eruption described in DS allows us to speculate that tooth size could increase with age; however, paradoxically, we observed progressive reductions in tooth sizes in the DS group, due mainly to reductions in crown height and mesiodistal diameter. It has been suggested that dental wear facets could be a predictive sign for the identification of persons with DS, corroborating the idea that a common consequence of clenching or grinding the teeth is their generalized wear.…”
Section: Discussionmentioning
confidence: 74%
“…However it has been reported that this variable only showed significantly changes in the late growth period (40 th decade of life), while no significant effects has been reported in young adults. 26,37 Since patients in this study were young adults, influence of sex could not be expected.…”
Section: Discussionmentioning
confidence: 98%